2020
DOI: 10.7150/thno.47980
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial injury and COVID-19: Serum hs-cTnI level in risk stratification and the prediction of 30-day fatality in COVID-19 patients with no prior cardiovascular disease

Abstract: Introduction: To explore the involvement of the cardiovascular system in coronavirus disease 2019 (COVID-19), we investigated whether myocardial injury occurred in COVID-19 patients and assessed the performance of serum high-sensitivity cardiac Troponin I (hs-cTnI) levels in predicting disease severity and 30-day in-hospital fatality. Methods: We included 244 COVID-19 patients, who were admitted to Renmin Hospital of Wuhan University with no preexisting cardiovascular disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 44 publications
(41 reference statements)
2
44
1
5
Order By: Relevance
“…Further, TnT levels had a significant correlation with CRP and plasma NTproBNP levels. Cao et al has shown that 11% of the COVID-19 patients had increased TnT levels, and these patients had no preexisting cardiovascular conditions (191). These data suggest that increased cardiac injury markers are likely due to viral-induced cardiac injury.…”
Section: Comparison Of Cardiovascular Conditions Associated With Sarsmentioning
confidence: 90%
“…Further, TnT levels had a significant correlation with CRP and plasma NTproBNP levels. Cao et al has shown that 11% of the COVID-19 patients had increased TnT levels, and these patients had no preexisting cardiovascular conditions (191). These data suggest that increased cardiac injury markers are likely due to viral-induced cardiac injury.…”
Section: Comparison Of Cardiovascular Conditions Associated With Sarsmentioning
confidence: 90%
“…Since clinical deterioration of COVID-19 is mostly accompanied by worsening pneumonia and development of ARDS, we recommend initiating TPE when there are signs of respiratory failure requiring mechanical ventilation. In particular, highly elevated ferritin levels in blood, and the estimation of myocardial injury using high-sensitivity cardiac troponin I may also be considered useful 114 , 115 .…”
Section: Treatment Of Cytokine Stormmentioning
confidence: 99%
“…Some patients exhibit pneumonia in both lungs, multi-organ failure, and even death 13 - 16 . Individuals who have severe health conditions, like cancer, cardiovascular diseases, diabetes, and pulmonary diseases, are at higher risk of SARS-CoV-2 infection 17 - 21 . At present, there is neither a vaccine nor specific antiviral treatments approved for COVID-19, but some medications have been authorized for emergency use in certain patients.…”
Section: Covid-19 Pandemicmentioning
confidence: 99%